Pendidikan Antikorupsi Melalui Pembelajaran PPKn di Sekolah Dasar - Afyfah Nurtisna; Melva Zainil (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Anti-corruption education is essential to be introduced from an early age as an effort to build honest, disciplined, and responsible character. Elementary school serves as a fundamental stage to instill these values through the subject of Civics Education (PPKn). This study uses a literature review method by analyzing relevant sources such as journals, books, and official policy documents. The aim is to identify the role of Civics Education in integrating anti-corruption values into elementary education. The findings indicate that Civics Education can serve as an effective medium to foster honesty, care, and responsibility through storytelling, discussions, and role-play methods. Support from teachers, schools, and families, as well as the development of contextual learning media, is needed to make anti-corruption values easier to understand and apply by elementary students.